Rubiane Maia’s drift between the body-territory in the Global South - Sousa, Sofia (Farol, 2024)
This article proposes a visual-content analysis of the Divisa Project by artist Rubiane Maia. Based on this artistic project, which is based on the creation of symbolic landmarks that mark the territorial drift between the territories of Espírito Santo and Minas Gerais, our main objective is to reflect and establish conceptions around the concepts of body-territory, displacement and local art, as resistances and memories - based on a process of resignification of the lived experiences of connection between the human body and the body-territory.